A CHIMERIC ANTIGEN CONSISTING OF TYPE III SECRETION PROTEINS AS A CHLAMYDIA VACCINE CANDIDATE - Liang, Steven (My University, 2019)
Chlamydia is the most prevalent sexually transmitted bacterial infection in many developed countries, including Canada. Untreated infections in women can lead to a number of complications including pelvic inflammatory disease, tubal factor infertility, and ectopic pregnancy. Public health programs, including screening for at-risk individuals, partner identification, and antibiotic treatment, have had limited success in controlling the rising incidence of chlamydial infections over the past two decades. A chlamydia vaccine that prevents infection and its pathological sequelae is the next essential step to control this persistent public health problem. Chlamydia spp. utilize the highly conserved type III secretion (T3S) system as an essential virulence factor for infection and intracellular replication. Here, we evaluated a novel chimeric antigen (BD584) consisting of three T3S proteins from C. trachomatis (CopB, CopD, and CT584) as a potential chlamydia vaccine candidate. Intranasal immunization with BD584 elicited strong humoral responses that neutralized infection in vitro. Following intravaginal challenge with C. muridarum, immunized mice had a 95% reduction in chlamydial shedding and a 87.5% reduction in incidence of upper genital tract pathology compared to control mice. BD584 immunization generated strong cell-mediated and mucosal antibody responses in mice with different genetic backgrounds, and conferred protection against an intravaginal C. trachomatis infection in two out of three strains of mice. BD584 formulated with NE01, a mucosal adjuvant known to be safe and effective in humans, was shown to be highly immunogenic and efficacious against C. trachomatis infection in mice. These results suggest that BD584 may represent a promising antigen for use in a chlamydia vaccine.
TYPE III SECRETION PROTEINS AS A CHLAMYDIA VACCINE CANDIDATE
Keywords: Chlamydia; Vaccine; Type III Secretion